Effects of post- oxidation annealing temperature on ZrO2 thin film deposited on 4H-SiC substrate - Kurniawan, T.; Wong, Y.H.; Cheong, K.Y.; Moon, J.H.; Bahng, W.; Razak, K.A.; Lockman, Z.; Kim, H.J.; Kim, N.K. (Elsevier, 2011)
ZrO2 thin film has been formed on n-type 4H-SiC substrate using a combination of metal sputtering (∼25 nm thick) and thermal oxidation (15 min at 500 °C) processes. Effects of post-oxidation annealing temperature (600–900 °C) on the physical and electrical properties of the thin film have been investigated. High resolution transmission electron microscopy attached with energy dispersive X-ray has been used to examine cross-sectional morphology and to study element chemical distribution of the investigated region. Selected area diffraction analysis has been employed to examine crystallinity of the samples. Metal-oxide-semiconductor capacitors have been fabricated to examine leakage current through the oxide using current–voltage measurement. Oxide-semiconductor interface-trap density has been extracted using capacitance–voltage measurement. The annealing process reduced leakage current density as low as one order of magnitude. However, breakdown voltage of the oxide has been reduced. Dielectric constant extracted from this work ranges from 22 to 80, depending on the annealing temperature.